KOMUNIKASI BRAND SILOAM HOSPITAL DALAM PEMASARAN LAYANAN KESEHATAN UNGGULAN - Sarwo Eddy Wibowo dan Aidar Erika Toding Pali (Prodi Ilmu Administrasi Negara, 2021)
Hospitals are non-profit organizations whose goals are humanitarian, but over time hospitals, especially private hospitals, in carrying out their organizational functions are inseparable from business. One of the private business-oriented hospitals is the Siloam hospital network. For the people of big cities, the name Siloam is familiar because considering the Lippo business group which is quite involved in running this health service business. This is inseparable from the brand communication made by Siloam in building networks, partners and acquisitions of Siloam hospitals throughout Indonesia. This research uses qualitative research methods with a descriptive approach. Siloam hospitals carry out brand communication in introducing identities, health care products, and services that will be provided by the hospital to the wider community through attributes, benefits, values, culture, personality, and service users.